Ecotourism and Climates changes: the ecolodge contribution in global warming mitigation - Luchman Hakim; Nobukazu Nakagoshi (Journal of Tropical Life Science, 2014)
Global attention to the global warming reduction has invite numerous strategy implemented with the objectives is mitigating greenhouse gasses emission which threats to the future of living in biosphere. Essentially, absorbing CO2 from atmosphere and sequestering in terrestrial ecosystem is one of the significant strategy. While in developing countries it is become essential, support for forest conservation, afforestation and effort to increase terrestrial ability to capture and storage carbon is poor. Ecotourism offer potential key to solved such problems by promoting ecolodge as a sustainable tourism accomodations. This paper aims to explore the potential of ecotourism sector to alleviate global warming and establishing framework for ecolodge planning and development in tropical developing countries. This paper highlight the significant of ecolodge attraction and development management to meet proper carbon capture and sequestration mechanism. The attraction management and developing programs ultimately able to increase plants biomass while accommodation able to practicing energy efficient and optimizing reuse and recycle approach. It will become the potential solution for reducing greenhouse gas emissions and create clean development strategy.